Thymosin participates in antimicrobial immunity in zebrafish. Issue 87 (April 2019) - Zou, Song-Song; Wang, Jing; Li, Bao-Xia; Yang, Gui-Wen; Sun, Jie-Jie; Yang, Hui-Ting
Abstract: Thymosin hormones, which were shown to be involved in immune system development and differentiation in previous studies, have antimicrobial functions in different animals. Zebrafish are a useful model for immunology research. Although thymosin has been reported to be involved in the embryonic development of zebrafish, it is necessary to uncover the antimicrobial function of thymosin in zebrafish. In this study, we expressed thymosin β (Tβ) in zebrafish in vitro and studied its antimicrobial function. The Tβ protein consists of 45 amino acids and is conserved among its family members, especially the actin-binding motif (LKKTET). Tβ was expressed in all tested tissues and was highly expressed in the brain, liver and hindgut. After Aeromonas hydrophila challenge, the Tβ transcript level increased in the skin, liver, kidney, spleen, thymus, foregut, gills and midgut. Purified recombinant thymosin β (rTβ) protein was used to study the antimicrobial mechanism. rTβ could inhibit the growth of Staphylococcus aureus, Aeromonas hydrophila, Vibrio anguillarum, Pseudomonas aeruginosa and Klebsiella pneumoniae . rTβ also binds to and agglutinates certain bacteria. Further study showed that rTβ could combine with the polysaccharides from gram-negative and gram-positive bacterial walls. All results suggested that the Tβ of zebrafish plays a significant role in innate antibacterial immune responses. Highlights: Tβ in zebrafish could participate in antibacterial innate immunity. Tβ expression was upregulated in zebrafish challenged by Aeromonas Hydrophila. Tβ could inhibit bacterial growth and bind to different bacteria and polysaccharides.